Electrode-free constrained annealing hafnium oxide-based ferroelectric film and preparation method and application thereof
By introducing Al doping into the HZO ferroelectric film and adopting electrode-free constraint annealing method, the problem of high dependence on electrode materials in the prior art is solved, and efficient preparation of ferroelectric films is achieved, and performance and durability are improved.
Patent Information
- Application Number
- CN202411830373.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The existing HZO ferroelectric films need to be annealed after plating with specific electrodes, resulting in a high dependence on electrode materials, increasing the production cost and the impact of the interface layer.
ALD technology is used to alternately deposit Hf0.5Zr0.5O2 films and Al2O3 films on the substrate, ferroelectricity is improved through Al doping, and high-temperature annealing is performed under electrode constraints to form a hafnium oxide-based ferroelectric film.
It achieves a high residual polarization strength under electrode constraints, reduces coercive fields, improves durability and stability, simplifies the preparation process and reduces costs.
Smart Images

Figure CN119615118A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field, and in particular relates to a hafnium oxide-based ferroelectric film subjected to electrode-free restraint annealing, and a preparation method and application thereof. Background Art
[0002] In this data-driven era, data storage has always been a hot topic of concern. In many high-tech fields such as high-performance computing, artificial intelligence and big data analysis, they all rely on the advancement of storage technology to improve system efficiency. Moreover, as the core link of information processing and storage, the performance of memory directly affects the efficiency of the entire system. However, the currently widely used memories have various shortcomings. For example, although SRAM is high-speed, it has high power consumption / high cost problems. DRAM has a large storage capacity but requires constant electrical refresh to ensure data security. Although Flash has a large storage capacity and is non-volatile, its write speed is very slow. Faced with such a background, developing more efficient storage technology has become an important task in the scientific and technological community.
[0003] Ferroelectric memory is expected to be the key to solving this problem. Ferroelectric memory represents different storage states based on the different polarization states of the ferroelectric layer, resulting in different device resistance values. Compared with traditional memory, ferroelectric memory has a series of advantages. First, it is non-volatile and can maintain its polarization state for up to 10 5 min, and it has extremely high read and write speeds, with some devices achieving a switching speed of 0.5ns at 5v. Its power consumption is very low, and the current density can be reduced to 10 when reading data. -6 A / cm 2 , it also has a longer write life, the optimized switching times can reach 10 11 Second-rate.
[0004] Currently, the most widely used ferroelectric materials are perovskite-based materials, such as lead zirconate titanate, barium titanate, strontium bismuth tantalate, etc. Although they have the advantage of large residual polarization intensity, they also have disadvantages. For example, large leakage current has greater power consumption; large frequency band offset has smaller bandwidth; the preparation process is incompatible with CMOS process, requiring additional production lines; large thickness, which is not conducive to integrated design, etc. In contrast, HfO2-based ferroelectric materials have the advantages of smaller leakage current, smaller frequency band offset, smaller thickness, and preparation process compatible with CMOS. Zr-doped HZO films also have higher residual polarization intensity and higher durability, and are expected to become the best choice for the next generation of memory materials.
[0005] However, the HZO films published so far all need to be rapidly annealed at a certain temperature under the condition of being plated with specific electrodes (such as TiN, W, Au, etc.), and the clamping effect of the electrodes on the HZO films can achieve a higher residual polarization strength. The strong demand for specific electrodes limits the structure of HZO films. For example, in the ferroelectric gate used to adjust the performance of two-dimensional CMOS devices, it means an additional interface layer, which seriously affects the performance of the device. In addition, the precious metal electrodes mean higher costs and additional process flows, which seriously affect the application of HZO films. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a hafnium oxide-based ferroelectric film with electrode-free annealing and a preparation method and application thereof, in order to solve the technical problem that the HZO ferroelectric film needs to be annealed after being plated with specific electrodes.
[0007] The present invention adopts the following technical solutions: A method for preparing a hafnium oxide-based ferroelectric thin film without electrode constraint annealing comprises the following steps: ALD technology is used to alternately deposit a set number of Hf layers on the substrate. 0.5 Zr 0.5 O2 film and a layer of Al2O3 film to obtain Al2O3 with different doping concentrations x -(Hf 0.5 Zr 0.5 O2) y Ferroelectric film, x represents the number of layers of Al2O3 deposited by ALD, y represents the number of layers of Hf deposited by ALD 0.5 Zr 0.5 The number of layers of O2; The Al x -(Hf 0.5 Zr 0.5 O2) y The ferroelectric film is annealed at high temperature to obtain Al x -(Hf 0.5 Zr 0.5 O2) y Ferroelectric thin film samples; The Al x -(Hf 0.5 Zr 0.5 O2) y The ferroelectric thin film sample is plated with a top electrode and a bottom electrode to obtain a hafnium oxide-based ferroelectric thin film.
[0008] Preferably, the ALD technique is used to alternately deposit a set number of layers of Hf on the substrate. 0.5 Zr 0.5 The O2 film and a layer of Al2O3 film are specifically: Using plasma enhanced atomic layer deposition technology, a certain number of Hf layers are alternately deposited on a p-type Si substrate. 0.5 Zr 0.5 O2 film; Plasma-enhanced atomic layer deposition technology was used to deposit a layer of Al2O3 film on the HZO film; Repeat until Al with a certain cycle ratio is generated x -(Hf 0.5 Zr 0.5 O2) y Ferroelectric thin films.
[0009] Preferably, [(CH3)2N]4Hf(TDMAH) is used as the Hf source, [(CH3)2N]4Zr(TDMAZ) is used as the Zr source, oxygen plasma is used as the oxygen source, the growth temperature is 220-300°C, 1 cycle of ZrO2 and 1 cycle of HfO2 are alternately grown on the substrate, and the alternate deposition is repeated y / 2 times to obtain a set thickness of Hf 0.5 Zr 0.5 O2 film.
[0010] Preferably, (CH3)3Al(TMA) is used as the Al source, oxygen plasma is used as the oxygen source, the growth temperature is 220-300°C, and Hf 0.5 Zr 0.5 A layer of Al2O3 film is grown on the O2 film to complete the Hf 0.5 Zr 0.5 Al doping of O2 thin films.
[0011] Preferably, the concentration of doped Al is 2.04% to 5.88%.
[0012] Preferably, the high temperature annealing conditions are specifically: In an oxygen atmosphere, at standard atmospheric pressure, the Al x -(Hf 0.5 Zr 0.5 O2) y The ferroelectric film is subjected to a high temperature annealing treatment at 500-700°C for 20-40s.
[0013] Preferably, the Al x -(Hf 0.5 Zr 0.5 O2) y The top electrode and bottom electrode of the ferroelectric thin film sample are specifically: The electrode material was used as the target material, and the bottom electrode and the dot top electrode with a diameter of 500~700μm were grown by magnetron sputtering coating process. The temperature was 0~300℃ and the argon partial pressure was 1.0~5.0×10 -1Pa, substrate rotation speed is 2~10rpm, sputtering power is 20~50W, and sputtering time is 2~4min.
[0014] Preferably, the thickness of the top electrode and the bottom electrode is 80-120 nm.
[0015] Another technical solution of the present invention is a hafnium oxide-based ferroelectric thin film that is annealed without electrode constraints.
[0016] Another technical solution of the present invention is to use the hafnium oxide-based ferroelectric thin film annealed without electrode restraint in resistive random access memory and ferroelectric field effect transistor.
[0017] Compared with the prior art, the present invention has at least the following beneficial effects: A method for preparing a hafnium oxide-based ferroelectric thin film without electrode constraint annealing, wherein the obtained Al-doped HZO thin film material has ferroelectricity. Compared with the prior art, a plasma enhanced atomic layer deposition process is used to overlap and grow HZO ferroelectric thin films and Al-doped thin films of different thicknesses and numbers of layers on a substrate, and the process is simple and controllable. On the one hand, the uniform Al-doped layer produces a clamping effect similar to that of an electrode, which promotes the formation of a ferroelectric orthorhombic phase of the HZO ferroelectric thin film during rapid annealing. On the other hand, the relatively small Al 3+ Replacement of Hf 4+ It causes lattice distortion in the HfO2 unit cell and promotes the formation of ferroelectric orthorhombic phase. Under the action of these two kinds of Al doping, the ferroelectricity of the HZO film is not only improved, but also the coercive field is greatly reduced, which improves the durability of the HZO ferroelectric film and enables the HZO film to achieve a higher residual polarization strength without annealing under electrode constraints.
[0018] Furthermore, by using ALD technology to alternately deposit a set number of layers of Hf on the substrate 0.5 Zr 0.5 O2 film and a layer of Al2O3 film to achieve Al element in Hf 0.5 Zr 0.5 Effective doping of O2 film is achieved through doping.
[0019] Furthermore, the concentration of Al doping greatly affects the Al x -(Hf 0.5 Zr 0.5 O2) y The ferroelectric properties of the film are x -(Hf 0.5 Zr 0.5 O2) y The film cannot form good ferroelectricity without electrode constraints. When the doping concentration is high, Al x -(Hf 0.5Zr 0.5 O2) y The film is easy to form antiferroelectric properties or paraelectric properties, so it is necessary to adjust the doping concentration of the Al element. When the Al doping concentration is 2.04%~5.88%, Al x -(Hf 0.5 Zr 0.5 O2) y The film can easily form good ferroelectric properties.
[0020] Furthermore, the annealing process of the sample was completed under the condition of no electrode constraint, which is beneficial to prevent the blocking effect of the electrode during annealing, and use the oxygen atmosphere to reduce the oxygen vacancy concentration of the sample, thereby reducing crystal defects, preventing the built-in electric field caused by crystal defects from hindering the polarization state transition of the ferroelectric domain of the ferroelectric film, inhibiting the wake-up effect of the ferroelectric film, and reducing the change in the residual polarization intensity of the ferroelectric film with the increase of the number of electric cycles under a certain number of initial electric cycles, which is beneficial to increase the effective switching times of the ferroelectric film and improve the stability of the ferroelectric film. At the same time, fewer defects improve the durability of the ferroelectric film and increase the life of the ferroelectric film.
[0021] In summary, the present invention is achieved by 0.5 Zr 0.5 A certain concentration of Al doping was introduced into the O2 film to achieve the preparation of Al with excellent ferroelectric properties under electrode-free conditions. x -(Hf 0.5 Zr 0.5 O2) y The invention not only significantly improves the cycle characteristics of the film, but also reduces the dependence of the hafnium oxide-based ferroelectric film on specific electrode materials, thereby simplifying the preparation process of the hafnium oxide-based ferroelectric film. In addition, the invention also reduces the preparation steps of the hafnium oxide-based ferroelectric film when integrating other devices (such as optoelectronic devices, sensors, etc.), broadening the application range of the hafnium oxide film; through this doping strategy, the ferroelectric properties of the film are optimized, which is of great significance for the development of high-performance non-volatile memory and other electronic devices.
[0022] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings to be used in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0024] Figure 1A flow chart of preparing a hafnium oxide-based ferroelectric thin film without electrode confinement annealing according to the present invention; Figure 2 The hysteresis loop diagram of the hafnium oxide-based ferroelectric thin film of Examples 1 to 4 provided by the present invention; Figure 3 The hysteresis loop diagrams of the hafnium oxide-based ferroelectric thin films of Examples 5 to 8 provided by the present invention; Figure 4 The hysteresis loop diagrams of the hafnium oxide-based ferroelectric thin films of Examples 9 to 12 provided by the present invention; Figure 5 The hysteresis loop and current-voltage curve of the hafnium oxide-based ferroelectric thin film of Example 6 provided by the present invention; Figure 6 This is a cycle characteristic curve diagram of the hafnium oxide-based ferroelectric thin film of Example 6 provided by the present invention. DETAILED DESCRIPTION
[0025] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.
[0027] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0028] In the present invention, unless otherwise specified, percentage (%) or part refers to the weight percentage or weight part relative to the composition.
[0029] In the present invention, unless otherwise specified, the components or preferred components involved can be combined with each other to form a new technical solution.
[0030] In the present invention, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "6-22" means that all real numbers between "6-22" have been listed in this document, and "6-22" is just an abbreviation of these numerical combinations.
[0031] The “range” disclosed in the present invention is in the form of a lower limit and an upper limit, which can be one or more lower limits, and one or more upper limits, respectively.
[0032] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0033] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the sequence. Preferably, the reaction method herein is carried out sequentially.
[0034] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.
[0035] The present invention provides a hafnium oxide-based ferroelectric film annealed without electrode constraint, and a preparation method and application thereof. There are no special requirements for electrode materials. Compared with other hafnium oxide-based ferroelectric films that need to be annealed under the clamping action of precious metal electrodes to achieve better performance, the present application can achieve it by annealing without electrode constraint. No special requirements for electrodes can save the cost of electrode materials and the process cost of electrode plating on the one hand. On the other hand, the ferroelectric film without electrode coverage means less interface effect in some application fields (such as two-dimensional CMOS). When applied, the sample proposed in the present application can maintain lower power consumption while maintaining higher performance, thereby saving costs.
[0036] The integration of HfO2-based ferroelectric material gates can not only effectively adjust the electrical, optical and mechanical properties of two-dimensional materials, but also facilitate the miniaturization of modern CMOS technology, significantly increasing transistor density. This progress has paved the way for the development of nanoelectronics, but the existing HfO2 material preparation technology requires annealing under electrode coverage, and the clamping effect of the electrode promotes the growth of the ferroelectric phase of the material. This results in the devices produced during application having additional interface effects due to the electrode layer, which affects the performance of the device. In addition, the electrodes required by the existing HfO2 material preparation technology are mostly precious metal electrodes, which also increases the material cost of the device.
[0037] See also Figure 1 The present invention provides a method for preparing a hafnium oxide-based ferroelectric thin film without electrode constraint annealing, comprising the following steps: S1, substrate pretreatment; S101, using alcohol and high-purity water to clean the heavily doped p-type Si substrate respectively; The substrate is any one of silicon dioxide / silicon, silicon, germanium, sapphire, mica or gold foil.
[0038] S102, ultrasonically cleaning the pre-cleaned p-type Si substrate, etching the Si substrate with an HF solution to remove the SiO2 oxide layer on the surface of the silicon wafer, and setting the cleaning time to 30 seconds; S103, clean the Si substrate again using alcohol and high-purity water respectively.
[0039] S2, using ALD technology on the p-type Si substrate obtained in step S1, alternately depositing a certain number of layers of Hf 0.5 Zr 0.5 O2 film and 1 layer of Al2O3 film to obtain Al2O3 with different doping concentrations x -(Hf 0.5 Zr 0.5 O2) y Ferroelectric thin film, where x represents the number of layers of Al2O3 deposited using ALD, and y represents the number of layers of Hf deposited using ALD 0.5 Zr 0.5 The number of layers of O2; S201, using plasma enhanced atomic layer deposition technology, alternately deposit a certain number of Hf layers on a p-type Si substrate 0.5 Zr 0.5 O2 film; Using [(CH3)2N]4Hf(TDMAH) as Hf source, [(CH3)2N]4Zr(TDMAZ) as Zr source, and oxygen plasma as oxygen source, the growth temperature is 220~300℃, and one cycle of ZrO2 and one cycle of HfO2 are alternately grown on a p-type Si substrate. Repeat the alternating deposition y / 2 times (uniform doping) to obtain a set thickness of Hf 0.5 Zr 0.5 O2 film; S202, using plasma enhanced atomic layer deposition technology to deposit a layer of Al2O3 film on the HZO film; (CH3)3Al(TMA) was used as Al source, oxygen plasma was used as oxygen source, the growth temperature was 220~300℃, and Hf 0.5 Zr 0.5 A layer of Al2O3 film is grown on the O2 film to complete the Hf 0.5 Zr 0.5 Al doping of O2 thin films.
[0040] Preferably, the concentration of doped Al is 2.04% to 5.88%.
[0041] S203, repeating the process of step S201 and step S202 until Al with a certain circulation ratio is generated x -(Hf 0.5 Zr 0.5 O2) y Ferroelectric thin films.
[0042] S3, performing high temperature annealing on the sample obtained in step S2; The sample obtained from S2 was subjected to high temperature annealing at 500-700°C for 20-40s at a heating rate of 40-60K / s under standard atmospheric pressure.
[0043] S4, plating a top electrode and a bottom electrode on the sample obtained in step S3 to obtain a hafnium oxide-based ferroelectric thin film.
[0044] The electrode material was used as the target material, and the bottom electrode and the dot top electrode with a diameter of 500~700μm were grown by magnetron sputtering coating process. The temperature was 0~300℃ and the argon partial pressure was 1.0~5.0×10 -1 Pa, substrate rotation speed is 2~10rpm, sputtering power is 20~50W, sputtering time is 2~4min, and the thickness of top electrode and bottom electrode is 80~120nm.
[0045] The electrode material is any one of common metal materials (such as Cu, Au), carbon-based materials (such as graphite, carbon nanotubes, etc.), alloy materials (such as Ni-Cr alloy, titanium alloy, etc.), and coating materials (such as platinum-plating, ITO).
[0046] A hafnium oxide-based ferroelectric film without electrode constraint annealing and its preparation method and application are prepared by the above method; the film has high residual polarization intensity, no obvious wake-up effect and high durability, and no special requirements for electrode materials. The film can be used to make devices such as resistive random access memory and ferroelectric field effect transistors.
[0047] The gold electrodeless confinement annealing hafnium oxide-based ferroelectric film of the present invention can be applied to resistive random access memory and ferroelectric field effect transistor.
[0048] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0049] The embodiments are all hafnium oxide-based ferroelectric thin films that are annealed without electrode confinement, which are manufactured by the above steps. The difference between different embodiments is the difference in Al doping concentration and the difference in annealing temperature of the samples in an oxygen atmosphere at a certain doping concentration.
[0050] Example 1: Al x -(Hf 0.5 Zr 0.5 O2) y The Al doping concentration of the ferroelectric film is 2.04%, and the sample is annealed at 400°C in an oxygen atmosphere.
[0051] Example 2: Al x -(Hf 0.5 Zr 0.5 O2) y The Al doping concentration of the ferroelectric film is 2.04%, and the sample is annealed at 500°C in an oxygen atmosphere.
[0052] Example 3: Al x -(Hf 0.5 Zr 0.5 O2) y The Al doping concentration of the ferroelectric film is 2.04%, and the sample is annealed at 600°C in an oxygen atmosphere.
[0053] Example 4: Al x -(Hf 0.5 Zr 0.5 O2) y The Al doping concentration of the ferroelectric film is 2.04%, and the sample is annealed at 700°C in an oxygen atmosphere.
[0054] Example 5: Al x -(Hf 0.5 Zr 0.5 O2) y The Al doping concentration of the ferroelectric film is 4%, and the sample is annealed at 400°C in an oxygen atmosphere.
[0055] Example 6: Al x -(Hf 0.5 Zr 0.5 O2) y The Al doping concentration of the ferroelectric film is 4%, and the sample is annealed at 500°C in an oxygen atmosphere.
[0056] Example 7: Al x -(Hf 0.5 Zr 0.5 O2) y The Al doping concentration of the ferroelectric film is 4%, and the sample is annealed at 600°C in an oxygen atmosphere.
[0057] Example 8: Al x -(Hf 0.5 Zr 0.5 O2) y The Al doping concentration of the ferroelectric film is 4%, and the sample is annealed at 700°C in an oxygen atmosphere.
[0058] Example 9: Al x -(Hf 0.5 Zr 0.5 O2) y The Al doping concentration of the ferroelectric film is 4%, and the sample is annealed at 400°C in an oxygen atmosphere.
[0059] Example 10: Al x -(Hf 0.5 Zr 0.5 O2) y The Al doping concentration of the ferroelectric film is 5.88%, and the sample is annealed at 500°C in an oxygen atmosphere.
[0060] Example 11: Al x -(Hf 0.5 Zr 0.5 O2) y The Al doping concentration of the ferroelectric film is 5.88%, and the sample is annealed at 600°C in an oxygen atmosphere.
[0061] Example 12: Al x -(Hf 0.5 Zr 0.5 O2) y The Al doping concentration of the ferroelectric film is 5.88%, and the sample is annealed at 700°C in an oxygen atmosphere.
[0062] See also Figure 2 , Figure 3 and Figure 4 It can be seen from the hysteresis loop diagram of the hafnium oxide-based ferroelectric thin film that the hafnium oxide-based ferroelectric thin film annealed without electrode confinement proposed in the present application exhibits certain ferroelectricity within the preferred doping concentration range.
[0063] from Figure 2 It can be seen that the Al-doped HZO film with a doping concentration of 2.04% has the highest remnant polarization intensity at an annealing temperature of 500℃~600℃, and its 2Pr reaches 21.4μC / cm 2 ; from Figure 3 It can be seen that the Al-doped HZO film with a doping concentration of 4% has the highest remnant polarization intensity at an annealing temperature of 500℃~600℃, and its 2Pr reaches 48.1μC / cm 2 ; from Figure 4 It can be seen that the Al-doped HZO film with a doping concentration of 5.88% has the highest remnant polarization intensity at an annealing temperature of 500℃~600℃, and its 2Pr reaches 24.5μC / cm 2 .
[0064] In general, the samples with Al doping concentration of 4% and annealing temperature of 500℃~600℃ showed the highest residual polarization intensity, and its polarization intensity was not weaker than that of the samples annealed under electrode covering conditions.
[0065] See also Figure 5 From the current-voltage curve of the hafnium oxide-based ferroelectric film, it can be seen that the hafnium oxide-based ferroelectric film annealed without electrode constraint in Example 6 exhibits an obvious ferroelectric characteristic peak under the conditions of annealing at 500° C. with an Al doping concentration of 4%.
[0066] See also Figure 6 From the cycle characteristic curve of Example 6, it can be seen that Example 6 has no obvious wake-up effect. 8 After the first cycle, the film still has a C / cm 2 The residual polarization intensity indicates that the hafnium oxide-based ferroelectric film annealed without electrode constraint proposed in this application has good cycle characteristics.
[0067] In summary, the present invention provides a hafnium oxide-based ferroelectric film annealed without electrode constraint, and a preparation method and application thereof, so that the uniform Al-doped layer of the sample produces a clamping effect similar to that of an electrode, promoting the formation of a ferroelectric orthorhombic phase in the HZO ferroelectric film during rapid annealing. On the other hand, the relatively small Al 3+ Replacement of Hf 4+ The HfO2 unit cell has lattice distortion and promotes the formation of the sample's ferroelectric orthorhombic phase. Under the action of these two Al doping, the HZO film not only has improved ferroelectricity, but also greatly reduced the coercive field, improved the durability of the HZO ferroelectric film, and made the HZO film reach a higher residual polarization intensity without annealing under electrode constraints. The technology provided by this application improves the performance of annealed ferroelectric films without electrode constraints, deepens people's understanding of the ferroelectric principle of HfO2 films, and promotes the development of new practical ferroelectric film fields.
[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a hafnium oxide-based ferroelectric thin film without electrode constraint annealing, characterized in that: The following steps are involved: ALD technology is used to alternately deposit a set number of Hf layers on the substrate. 0.5 Zr 0.5 O2 film and a layer of Al2O3 film to obtain Al2O3 with different doping concentrations x -(Hf 0.5 Zr 0.5 O2) y Ferroelectric film, x represents the number of layers of Al2O3 deposited by ALD, y represents the number of layers of Hf deposited by ALD 0.5 Zr 0.5 The number of layers of O2; The Al x -(Hf 0.5 Zr 0.5 O2) y The ferroelectric film is annealed at high temperature to obtain Al x -(Hf 0.5 Zr 0.5 O2) y Ferroelectric thin film samples; The Al x -(Hf 0.5 Zr 0.5 O2) y The ferroelectric thin film sample is plated with a top electrode and a bottom electrode to obtain a hafnium oxide-based ferroelectric thin film.
2. The method for preparing a hafnium oxide-based ferroelectric thin film by electrode-free annealing according to claim 1, characterized in that: ALD technology is used to alternately deposit a set number of Hf layers on the substrate. 0.5 Zr 0.5 The O2 film and a layer of Al2O3 film are specifically: Using plasma enhanced atomic layer deposition technology, a certain number of Hf layers are alternately deposited on a p-type Si substrate. 0.5 Zr 0.5 O2 film; Plasma-enhanced atomic layer deposition technology was used to deposit a layer of Al2O3 film on the HZO film; Repeat until Al with a certain cycle ratio is generated x -(Hf 0.5 Zr 0.5 O2) y Ferroelectric thin films.
3. The method for preparing a hafnium oxide-based ferroelectric thin film by electrode-free annealing according to claim 2, characterized in that: Using [(CH3)2N]4Hf(TDMAH) as Hf source, [(CH3)2N]4Zr(TDMAZ) as Zr source, and oxygen plasma as oxygen source, the growth temperature is 220~300℃, and one cycle of ZrO2 and one cycle of HfO2 are alternately grown on the substrate. Repeat the alternating deposition y / 2 times to obtain a set thickness of Hf 0.5 Zr 0.5 O2 film.
4. The method for preparing a hafnium oxide-based ferroelectric thin film by electrode-free annealing according to claim 2, characterized in that: (CH3)3Al(TMA) was used as Al source, oxygen plasma was used as oxygen source, the growth temperature was 220~300℃, and Hf 0.5 Zr 0.5 A layer of Al2O3 film is grown on the O2 film to complete the Hf 0.5 Zr 0.5 Al doping of O2 thin films.
5. The method for preparing a hafnium oxide-based ferroelectric thin film by electrode-free annealing according to claim 4, characterized in that: The concentration of doped Al is 2.04%~5.88%.
6. The method for preparing a hafnium oxide-based ferroelectric thin film by electrode-free confinement annealing according to claim 1, characterized in that: The high temperature annealing conditions are specifically as follows: In an oxygen atmosphere, at standard atmospheric pressure, the Al x -(Hf 0.5 Zr 0.5 O2) y The ferroelectric film is subjected to a high temperature annealing treatment at 500-700°C for 20-40s.
7. The method for preparing a hafnium oxide-based ferroelectric thin film by electrode-free annealing according to claim 1, characterized in that: The Al x -(Hf 0.5 Zr 0.5 O2) y The top electrode and bottom electrode of the ferroelectric thin film sample are specifically: The electrode material was used as the target material, and the bottom electrode and the dot top electrode with a diameter of 500~700μm were grown by magnetron sputtering coating process. The temperature was 0~300℃ and the argon partial pressure was 1.0~5.0×10 -1 Pa, substrate rotation speed is 2~10rpm, sputtering power is 20~50W, and sputtering time is 2~4min.
8. The method for preparing a hafnium oxide-based ferroelectric thin film by electrodeless confinement annealing according to claim 7, characterized in that: The thickness of the top electrode and the bottom electrode is 80 to 120 nm.
9. A hafnium oxide-based ferroelectric thin film prepared by the method according to any one of claims 1 to 8 and subjected to electrode-free confinement annealing.
10. Application of the hafnium oxide-based ferroelectric thin film subjected to electrodeless confinement annealing according to claim 9 in resistive random access memory and ferroelectric field effect transistor.
Citation Information
Patent Citations
Preparation method of hafnium oxide-based ferroelectric film
CN110890272A
Method for preparing Al-doped Hf < 0.5 > Zr < 0.5 > O < 2 > ferroelectric film capacitor by using PLD
CN111370576A
Method for inducing ferroelectricity of hafnium zirconium oxide film by using aluminum oxide dielectric film layer
CN112038212A
HfO2-based ferroelectric tunnel junction nerve synapse device and preparation method thereof
CN113346018A
Hafnium oxide-based ferroelectric film, preparation method and application
CN114400179A